THE ROLE OF GAMIFICATION IN THE MODERN EDUCATIONAL PROCESS (Academia Science Repository, 2023)
This article talks about modern education, the use of gamification, the practice of introducing game elements into education in different countries of the world. Also, the issues of organizing the educational process with the help of gamification, using gamification as an educational innovation, the versatile possibilities of gamification are studied, including programs and platforms that partially or fully use gamification elements in the process of creating educational resources. opinions are also given. The experiences of foreign scientists on the use of gamification in the educational process are analyzed.